Assessment of Late Sown Wheat (Triticum aestivum L.) Genotypes under High Temperature Stress Conditions - Bohara, Suman; Acharya, Basistha; Bohora, Surakshya; Upadhyaya, Jharana (Journal of Agriculture and Environment, 2023)
In recent years, climate change has led to an increase in extreme weather conditions, including high-temperature stress. High temperature stress is the term for an increase in temperature (> 30°C) following anthesis during grain development. Wheat is particularly vulnerable to high temperature stress, and its productivity is severely affected. With the objective of identifying wheat genotypes tolerant to heat stress in terms of grain yield, a total of fifty wheat genotypes were evaluated under heat stress conditions at Directorate of Agricultural Research, Lumbini Province, Khajura, Banke in 2021/22. There was highly significant difference (